2012
DOI: 10.1177/0954008312460065
|View full text |Cite
|
Sign up to set email alerts
|

Composite proton conducting membrane by radiation-induced grafting of 1-vinylimidazole onto poly(ethylene-co-tetrafluoroethylene) and phosphoric acid doping

Abstract: Composite membrane containing phosphoric acid (PA) for possible use in a fuel cell was prepared by radiation-induced grafting of 1-vinylimidazole (1-VIm) onto poly(ethylene-co-tetrafluoroethylene) (ETFE) films followed by protonation with PA doping. The preparation procedure involved three steps: (i) irradiation of ETFE films by an electron beam, (ii) grafting of 1-VIm onto the irradiated films under selected conditions and (iii) doping the grafted film with PA. The membrane composition, thermal properties and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 17 publications
(25 reference statements)
1
21
0
Order By: Relevance
“…As an example, poly(ethylene-alt-tetrafluoroethylene) (ETFE) was used [8,[52][53][54][55][56][57][58][59]. Generally, the polymer backbone material was irradiated and subsequently grafted with basic monomer(s), since it was anticipated that the affinity to PA scales with basicity.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, poly(ethylene-alt-tetrafluoroethylene) (ETFE) was used [8,[52][53][54][55][56][57][58][59]. Generally, the polymer backbone material was irradiated and subsequently grafted with basic monomer(s), since it was anticipated that the affinity to PA scales with basicity.…”
Section: Introductionmentioning
confidence: 99%
“…The membranes achieved very high proton conductivity with 140 mS/cm at low humidity [186]. This method proved to be simpler and had fewer problems than methods involving synthesis by polymerization reactions for obtaining similar membranes [18,92].…”
Section: Proton-exchange Membranes For High Temperature Fuel Cells Bymentioning
confidence: 99%
“…Engineering plastics have become the subject of many studies of developing proton exchange membranes used in fuel cells, which involve polytetrafluoroethylene (PTFE), poly(tetrafluoroethylene-co-hexafluoropropylene) (FEP), poly(tetrafluoroethylene-co-perfluoropropylvinylether) (PFA), poly(ethylene-alt-tetrafluoroethylene) (ETFE), poly(ether ether ketone) (PEEK), and poly(vinylidene fluoride) (PVDF) films. In these studies, the base film was modified via 2 Journal of Chemistry grafting using UV-light, -rays, electron beam, X-ray, and gamma radiation techniques [3,9,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Previously, Asano et al reported on the development of proton-conducting membranes generated by the -ray radiation grafting of styrene and its derivatives onto fluorine-containing base films and subsequent sulfonation [12,15,22,27].…”
Section: Introductionmentioning
confidence: 99%
“…The proton transport occurs between hydrogen bonds of neighboring heterocyclic units through structure diffusion [1,3,6,7,10]. However, studies on grafted films containing readily available Nheterocyclic monomers are very rare [23][24][25]29]. Recently, Schmidt and Schmidt-Naake reported on the preparation of phosphoric acid (PA) doped 4-vinylpyridine (4VP) grafted poly(ethylene-co-tetrafluoroethylene), ETFE-graftpoly(4VP), by using radiation-induced grafting method [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation